Plant Functional Traits: Soil and Ecosystem Services - Faucon, Michel-Pierre; Houben, David; Lambers, Hans (Trends in plant science, 2017)
Decline of ecosystem services has triggered numerous studies aiming at developing more sustainable agricultural management practices. Some agricultural practices may improve soil properties by expanding plant biodiversity. However, sustainable management of agroecosystems should be performed from a functional plant trait perspective. Advances in functional ecology, especially plant functional trait effects on ecosystem processes and services, provide pivotal knowledge for ecological intensification of agriculture; this approach acknowledges that a crop field is an agroecosystem whose ecological processes influence soil properties. We highlight the links between plant functional traits and soil properties in relation to four major ecosystem processes involved in vital ecosystem services: food production, crop protection, climate change mitigation, and soil and water conservation, aiming towards ecological intensification of sustainable agricultural and soil management. Agroecological studies build on the concept that, by understanding ecological processes, agroecosystems can be managed to produce more biomass more sustainably, and thus protect natural resources. Many studies in agroecology suggest that some agricultural practices can improve soil quality and restore agroecosystems by enhancing plant biodiversity. Functional plant traits to assess ecosystem processes and services can be used towards sustainable management of agroecosystems. Knowledge of the links between functional plant traits and soil carbon dynamics and sequestration, soil structural stability and soil erosion, soil nutrient dynamics and availability, and the abundance and diversity of soil microbial pathogens is essential for the development of agroecological principles.